A Framework For Studying The Individual Related Factors Contributing To The In Home Country Adjustment Among Repatriate Spouses And Children. - Ali, Anees Janee; Cheng, Wei Hin; Ismail, Mahazir; Mohd Yusoff, Yusliza (2005)
This manuscript has the objectives of producing a framework of repatriate spouses and children adjustment and presenting propositions for the benefits of future research. There are many variables that are related to repatriate spouses and children adjustment to their home country. However, individual related factors contributing to the adjustment of repatriate spouses and children are the main focus variables of this manuscript. The individual related factors that will be discussed are personality characteristics, attachment• styles, individual preferences and motivation, and individual satisfaction.